2020
DOI: 10.1371/journal.pntd.0008330
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping using new AFLP markers to explore intraspecific variation among pathogenic Sporothrix species

Abstract: Sporotrichosis is a chronic subcutaneous mycosis caused by Sporothrix species, of which the main aetiological agents are S. brasiliensis, S. schenckii, and S. globosa. Infection occurs after a traumatic inoculation of Sporothrix propagules in mammals' skin and can follow either a classic route through traumatic inoculation by plant debris (e.g., S. schenckii and S. globosa) or an alternative route through zoonotic transmission from animals (e.g., S. brasiliensis). Epizootics followed by a zoonotic route occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 91 publications
(221 reference statements)
3
40
0
Order By: Relevance
“…The mating‐type characterisation in both species revealed a skewed ratio between the MAT1‐1 : MAT1‐2 idiomorphs, with a predominance of MAT1‐2 isolates. As asexual amplification can skew mating frequencies, our results suggest that S brasiliensis genotypes during outbreaks in the feline population are likely to be predominantly clonal, which does not necessarily imply the absence of sex but indicates the emergence of a successful genotype 29 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The mating‐type characterisation in both species revealed a skewed ratio between the MAT1‐1 : MAT1‐2 idiomorphs, with a predominance of MAT1‐2 isolates. As asexual amplification can skew mating frequencies, our results suggest that S brasiliensis genotypes during outbreaks in the feline population are likely to be predominantly clonal, which does not necessarily imply the absence of sex but indicates the emergence of a successful genotype 29 …”
Section: Discussionmentioning
confidence: 82%
“…isolates. As asexual amplification can skew mating frequencies, our results suggest that S brasiliensis genotypes during outbreaks in the feline population are likely to be predominantly clonal, which does not necessarily imply the absence of sex but indicates the emergence of a successful genotype 29. The distribution pattern of the clinical Sporothrix isolates evaluated suggests how the mating-type between Sporothrix species is widespread in Espírito Santo, proposed two distinct scenarios of the disease in the state.…”
mentioning
confidence: 74%
“…Our analysis showed that the fragments observed following AFLP with EcoRI-AC / MseI-CT or EcoRI-AT / MseI-CT primers represent the optimal combinations to explore genetic diversity in Paracoccidioides. A similar in silico framework has been successfully applied for medically relevant Sporothrix species ( de Carvalho et al. 2020 , 2021a ), supporting that combining bioinformatics tools and whole-genome sequences can make the AFLP method more predictable instead of, rather, using random combinations of suboptimal endonuclease-combinations ( Rombauts et al.…”
Section: Discussionmentioning
confidence: 91%
“…All oligonucleotides were provided by Applied Biosystems in the AFLP Microbial Fingerprinting kit. AFLP fragments were determined by capillary electrophoresis with an ABI3730 Genetic Analyzer alongside a GeneScan 500 ROX internal size standard (35–500 bp; Applied Biosystems) at the Human Genome and Stem Cell Research Centre Core Facility (University of São Paulo, São Paulo, Brazil) under previously described conditions ( de Carvalho et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To perform the AFLP, we followed the protocol of Vos et al. 1995 with modifications described by de Carvalho et al. 2020 .…”
Section: Methodsmentioning
confidence: 99%